The mitochondrial genome of the land snail Theba pisana (Müller, 1774) (Stylommatophora: Helicidae): the first complete sequence in the genus Theba. Issue 2 (3rd July 2018) - Wang, Pei; Yang, Shan-Ping; Lin, Jun-Hong; Zhang, Ming-Zhe; Zhou, Wei-Chuan
Abstract: The complete mitochondrial genome of the white garden snail Theba pisana (Müller, 1774) has been sequenced and annotated in this study. The entire circular genome is 14, 795 bp in size and represents the first mitochondrial genome in the genus Theba, with two ribosomal RNA genes, 22 transfer RNA genes, 13 protein coding genes. All of genes are divided into two groups, including 24 genes on the majority coding strand (J strand) and others on the minority coding strand (N strand).The phylogeny supports the relationship of species in Helicidae.